Energy Design Guidelines for High Performance Schools: Arctic and Subarctic Climates - United States. Department of Energy. (National Renewable Energy Laboratory (U.S.), 2004)
The Energy Design Guidelines for High Performance Schools--Arctic and Subarctic Climates provides school boards, administrators, and design staff with guidance to help them make informed decisions about energy and environmental issues important to school systems and communities. These design guidelines outline high performance principles for the new or retrofit design of your K-12 school in arctic and subarctic climates. By incorporating energy improvements into their construction or renovation plans, schools can significantly reduce energy consumption and costs.